2022
DOI: 10.1155/2022/7828230
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Risk Factors of Coagulation Dysfunction and Hemorrhage in Newly Diagnosed Hyperleukocytic Acute Myeloma Leukemia

Abstract: Purpose. To explore whether and why abnormal coagulation function and hemorrhage can appear in patients with hyperleukocytic acute myeloid leukemia (HAML). Method. We retrospectively reviewed the charts of 724 acute myeloid leukemia (AML) patients admitted with a white blood cell count of >100 × 109/L between 2010 and 2019 in order to analyze the coagulation index of patients with HAML and explore the correlation of abnormal coagulation. Result. Prothrombin time (PT) was extended in group HAML compared with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
1
0
0
Order By: Relevance
“…A prior study of patients with AML showed significant increase of PT and APTT, similar to our results, as did another in CML patients. 29,30 Another study that agrees with our results reported that patients with CML had a higher prevalence of abnormal PT and abnormal APTT compared to healthy controls, which the authors suggested may be due to the effects of CML on the production and function of clotting factors. The prolongation of PT in CML patients is attributable to reduced levels of Factor VII; meanwhile, prolonged APTT may be due to deficiency of Factor VIII.…”
supporting
confidence: 90%
“…A prior study of patients with AML showed significant increase of PT and APTT, similar to our results, as did another in CML patients. 29,30 Another study that agrees with our results reported that patients with CML had a higher prevalence of abnormal PT and abnormal APTT compared to healthy controls, which the authors suggested may be due to the effects of CML on the production and function of clotting factors. The prolongation of PT in CML patients is attributable to reduced levels of Factor VII; meanwhile, prolonged APTT may be due to deficiency of Factor VIII.…”
supporting
confidence: 90%